THE PIDGIN AND CREOLE PHENOMENON AS A BRIDGE OF COMMUNICATION AMIDST LANGUAGE DIFFERENCES IN INDONESIA - Ani Sumaeratu Aini, Diana Maulidiya Almaidatuzakiyyah, Puput Nopitasari, Eneng Liah Khoiriyah (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2025)
Indonesia has a diversity of languages spoken by various ethnic groups, which often poses challenges for cross-language communication. Pidgin and creole are important solutions to overcome these barriers, serving as communication tools that connect individuals from different language backgrounds. This research examines the role of pidgin and creole in shaping the social and cultural identity of Indonesian society. Using a descriptive qualitative approach and a literature study, this research analyzes various literatures that describe the role of these languages in social life. The results show that pidgin and creole are not only practical communication tools, but also symbols of the social, historical and cultural dynamics of the people who use them. In the Indonesian context, these two languages function as social identities and communication bridges amidst language differences.